CRITICAL ANALYSIS OF DIETARY INTERVENTIONS FOR MANAGING HYPERTENSION IN ELDERLY PATIENTS. - Nayef Masoud Ali Alqahtani, Mohammad Abed Obed Alhazmi, Hend Aiadh Alamri, Fahd Hamdan Alsaedi, Tareq Hamed Alsaedi, Mohammad Saud Al-Sahli, Sami Adburrahman Ayed Aloufi, Rabie Awad Al-Harbi (Chelonian Research Foundation, 2022)
Hypertension, or high blood pressure, is one of the most common diseases in the aging population and is linked to many serious health consequences if there is a there is a lack of adequate management. This study, while critically examining several targeted dietary strategies that serve to manage hypertension among elderly patients, will do so. Nutritional strategies are presented for an informative literature survey, method overview, and results analysis accompanied by deficits, usefulness, and recommendations. Some key findings show that dietary suppression strategies such as the DASH (Dietary Approaches to Stop Hypertension) diet, low-sodium diets, potassium rise consumption, and closely observing the Meditate diet by the elderly provide successful results in hypertension control. Meanwhile, some differences may limit the effective implementation of these approaches, such as cultural preference and social and economic factors, which may also affect individuals' commitment. Therefore, the paper proposes guidelines for care providers, concerned parties, and individuals to improve dietary options and intervention outcomes for older people with high blood pressure. Keywords: Hypertension, Elderly Patients, Dietary Interventions, DASH Diet, Sodium Intake, Potassium Consumption, Mediterranean Diet.